Research Trends in Green Synthesis of CeO2 Nanoparticles: A Bibliometric Review - Prihatiningsih, Elisa; Sagadevan, Suresh; Nisha, Mehru; Fatimah, Is (Science and Technology Indonesia, 2026)
This bibliometric review examines the trends in green synthesis of CeO2 nanoparticles (NPs) emphasizing significant contributions and emerging research applications. Through an analysis of keywords, co-authorship networks, countries, and affiliation metworks, findings highlight that green synthesis of nanoparticles, applications of CeO2 as antibacterial agent, catalyst, and photocatalysts are the most used keywords reflecting strong interests. By evaluating the citation metrics within last 20 years, it could be concluded that green synthesis of CeO2 still have position to fill the map on the use of nanoparticles for various applications, mainly in medicine and environmental engineering. Stronger collaborations to explore linkages for creating new route as greener and sustainable method as innovation are still required.